INVARIABLE RESULT OF LIFE-LONG EDUCATION - Andrey A. Verbitskiy; Natalya A. Rybakina (Moscow Polytechnic University, 2016)
The article analyzes from the standpoint of the contextual approach the problems of realization of the main ideas of life-long education; substantiates the necessity to differentiate the notions of system and processes of life-long education. The authors treat the competence as an invariant result of student's activity on the different levels of life-long education system.